2003
DOI: 10.1177/002199803035184
|View full text |Cite
|
Sign up to set email alerts
|

Cured Shape of Cross-Ply Composite Thin Shells

Abstract: For a composite laminated plate, it has been found that classical laminate theory (CLT) can not always predict the final cured shape correctly and geometric nonlinearity must be considered. For composite laminated shells, experiments show that the cured shape depends on stacking sequence, radius, thickness, and size. This paper investigates the cured shape of several cross-ply composite shells. The cured shape of a cross-ply shell is generally cylindrical. A model is established to predict the cured shape. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 9 publications
(9 reference statements)
1
35
0
Order By: Relevance
“…It is potentially suitable for a wide variety of systems, such as morphing aircraft (Yokozeki et al, 2006;Diaconu et al, 2008;Schultz, 2008), deployable structures (Lei & Yao, 2010) and mechanical switches. The studies of multi-stable structures reported in open literatures are dominated by the bi-stable unsymmetric composite laminates (Jun & Hong, 1992 Hyer, 1998;Maenghyo et al,1998;Hufenbach et al, 2002Hufenbach et al, , 2006Ren, & Parvizi-Majidi, 2003Gigliotti et al, 2004;Dai et al 2007;Etches etal., 2009). A typical bi-stable composite laminate is shown as in Fig.1, which means that applying an external force the room temperature cylindrical shape can be snapped into another cylinder with curvature of equal magnitude and opposite sign.…”
Section: Conception Of Multi-stable Structuresmentioning
confidence: 99%
“…It is potentially suitable for a wide variety of systems, such as morphing aircraft (Yokozeki et al, 2006;Diaconu et al, 2008;Schultz, 2008), deployable structures (Lei & Yao, 2010) and mechanical switches. The studies of multi-stable structures reported in open literatures are dominated by the bi-stable unsymmetric composite laminates (Jun & Hong, 1992 Hyer, 1998;Maenghyo et al,1998;Hufenbach et al, 2002Hufenbach et al, , 2006Ren, & Parvizi-Majidi, 2003Gigliotti et al, 2004;Dai et al 2007;Etches etal., 2009). A typical bi-stable composite laminate is shown as in Fig.1, which means that applying an external force the room temperature cylindrical shape can be snapped into another cylinder with curvature of equal magnitude and opposite sign.…”
Section: Conception Of Multi-stable Structuresmentioning
confidence: 99%
“…Bistable composites have two stable shape (cylindrical shapes [1][2][3][4][5][6][7] or saddle shapes [8]) as a result of the coupling effect between their residual stress and geometric nonlinearity. These composites can be snapped through (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, Hyer [1,3] proposed the model for cross-ply laminate which is based on the polynomial displacement field and von-Karman non-linearity. This analytical modeling technique proposed by Hyer has been extended to various bistable panel problems, such as approximation of bifurcation temperature/side length [4][5][6], deformation behavior of angle-ply laminate [6,7], slippage effect between laminate and tool plate [8,9], identification of snap-though force [10,11], and initial curvature effect [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of initial curvature on bistable structures has been discussed by Ren et al [12], Pirrera et al [13], and Ryu et al [14]. Ryu et al [14] shows that the final curvature of a bistable CFRP cross-ply laminate can be easily predicted because the final curvature of the laminate with initial curvature can be expressed as the sum of the tool-plate curvature and final curvature of the laminate without initial curvature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation